Implementation of Natural Feature Tracking in Eclipse Applications Using Augmented Reality - Awan, Diky Rizky; Muliantara, Agus; Wibawa, I Gede Arta; Pramartha, Cokorda Rai Adi; Dwidasmara, Ida Bagus Gede; Suputra, I Putu Gede Hendra (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 3 (2023): JELIKU Volume 11 No 3, February 2023, 2022)
An eclipse is a phenomenon that occurs when a celestial body moves into the shadow of another celestial body, be it a solar eclipse or a lunar eclipse. In the process of understanding this phenomenon, people do not understand what is meant by the eclipse phenomenon. Because of this, we need a teaching aid to help us understand the material. The application will apply Augmented Reality technology using the Natural Feature Tracking (NFT) method. The application in this research will be made in the form of a native website. With python 3.7.0 64-bit programming language using the IDE (integrated development engineer), namely Visual Studio Code. This application will take advantage of the flask frameworks. This website will be native. Application implementation using native website templates with HTML (Hypertext Markup Language), CSS (Cascading Style Sheets), and Javascript. This application will be intended for a platform website resolution of 16:9 with a breakdown of 1920 x 1080 pixels. However, this ratio will be able to adjust because it applies the bootstrap 4 framework. From some tests conducted, the percentage of accuracy of the percentage of 3D object appearance is 52% on objects performing in the correct position, 34% on objects performing in the wrong position, and 10.67% on objects not appearing. In terms of functions, it has been running and meets the requirements with black box testing with 100% accuracy which is carried out based on 9 functions in the use case diagram.